2009
DOI: 10.1096/fj.08-124495
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 1 mediates fetal‐maternal dialogue regulating endometrial leukemia inhibitory factor

Abstract: Implantation requires communication between a receptive endometrium and a healthy blastocyst. This maternal-embryonic crosstalk involves local mediators within the uterine microenvironment. We demonstrate that a secreted protein, prokineticin 1 (PROK1), is expressed in the receptive endometrium and during early pregnancy. PROK1 induces expression of leukemia inhibitory factor (LIF) in endometrial epithelial cells and first trimester decidua via a Gq-Ca2+-cSrc-mitogen-activated protein kinase kinase-mediated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 38 publications
(59 reference statements)
3
105
1
5
Order By: Relevance
“…13 Furthermore, PROK1 was recently reported to enhance the adhesion of human trophoblast cells to extracellular matrix proteins. 15 This effect was shown to be mediated through PROK1 upregulation of LIF, suggesting that increased PROK1 activity may result in enhanced endometrial receptivity. PROKs are potent angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Furthermore, PROK1 was recently reported to enhance the adhesion of human trophoblast cells to extracellular matrix proteins. 15 This effect was shown to be mediated through PROK1 upregulation of LIF, suggesting that increased PROK1 activity may result in enhanced endometrial receptivity. PROKs are potent angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…10 The difficulty in studying implantation is that tissues are collected after an implantation event has occurred, making it hard to ascertain whether differences observed are the result of a predisposing factor or implantation itself. However, our previous findings, 10 together with the purported roles of PROK1 in intrauterine implantation, [13][14][15] led us to hypothesize that dysregulated PROKR1 expression might predispose the tubal environment to ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…EG-VEGF may support pregnancy through angiogenesis and VP regulation [5,25]. It has been reported that EG-VEGF is expressed in human periimplantation endometrium, which expression and receptor are elevated in human decidua during early pregnancy, and that EG-VEGF can mediate fetal-maternal dialogue by regulating hCG-mediated endometrial LIF expression [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that EG-VEGF, but not PROK2, expression peaks during the midluteal window of implantation, with immunolocalization to endometrial glandular epithelium, stromal and endothelial cells, and myometrial vascular endothelium as well as smooth muscle (Evans et al, 2009,Ngan et al, 2006. In addition, it has been suggested that EG-VEGF could have a role in mediating the dysregulated vascular permeability that occur in ovarian hyperstimulation syndrome.…”
Section: Eg-vegf and Implantationmentioning
confidence: 99%